Efficient production of superior dumbbell-shaped DNA minimal vectors for small hairpin RNA expression. Issue 18 (10th October 2015) - Yu, Han; Jiang, Xiaoou; Tan, Kar Tong; Hang, Liting; Patzel, Volker
Abstract: Genetic therapy holds great promise for the treatment of inherited or acquired genetic diseases; however, its breakthrough is hampered by the lack of suitable gene delivery systems. Dumbbell-shaped DNA minimal vectors represent an attractive, safe alternative to the commonly used viral vectors which are fraught with risk, but dumbbell generation appears to be costly and time-consuming. We developed a new PCR-based method for dumbbell production which comprises only two steps. First, PCR amplification of the therapeutic expression cassette using chemically modified primers to form a ready-to-ligate DNA structure; and second, a highly efficient intramolecular ligation reaction. Compared with conventional strategies, the new method produces dumbbell vectors more rapidly, with higher yields and purity, and at lower costs. In addition, such produced small hairpin RNA expressing dumbbells triggered superior target gene knockdown compared with conventionally produced dumbbells or plasmids. Our novel method is suitable for large-scale dumbbell production and can facilitate clinical applications of this vector system.